The influence of liquidity ratio as current (CR), (DER) rasio leverage and asset structure to return on investment of coal companies - Zian Fachrian; Wastam Wahyu Hidayat (Goodwood Publishing, 2023)
Purpose: This study objectives to determine whether or not there is an effect of Liquidity Ratio as Current (CR), (DER) Rasio Leverage and Assets Structure on Return On Investment. Research methodology: This lookup was once carried out on information collection on the economic reviews of coal organizations in the 2017-2021 period. This lookup makes use of quantitative methods. The sampling approach used in this find out was once purposive sampling. forty samples have been taken from eight coal businesses from the annual report. This learns about makes use of SPSS 26 as an analytical tool. Results: The effects of the partial check exhibit that Liquidity Ratio as Current (CR) has no giant impact on Return On Investment, (DER) Rasio Leverage has a large impact on Return On Investment, Assets Structure has no considerable impact on Return On Investment, whilst lookup in simultaneous assessments suggests that Liquidity Ratio as Current (CR), (DER) Rasio Leverage and Assets Structure have no sizable impact on Return On Investment. Conclusion: The study concludes that only the Debt to Equity Ratio (DER) has a significant effect on Return on Investment (ROI), while the Current Ratio and Asset Structure do not. Simultaneously, all three variables combined also show no significant impact on ROI. This indicates that DER is a key factor in influencing ROI among coal companies during the 2017–2021 period. Limitations: This research was conducted in coal sector companies listed on the Indonesia Stock Exchange, only 8 companies were studied and the financial reports analyzed were from only 5 years starting from 2017-2021, the results of the analysis of the remaining data were obtained as is. Contribution: This research can be useful for companies in order to determine policies to increase the company's investment value.